Regular exercise throughout pregnancy is associated with a shorter first stage of labor - Perales, María; Calabria, Irene; López, Carmina; Franco Álvarez Álvarez, Evelia; Coterón López, Javier; Barakat, Rubén (My University)
En el presente trabajo se examinó la influencia del ejercicio físico moderado durante el embarazo sobre la duración de las diferentes partes del parto

Purpose. The aim of the present study was to examine the influence of moderate physical exercise throughout pregnancy on the duration of labor stages. Design. Study was a randomized controlled trial. Setting. The study took place at Hospital Puerto de Hierro and Hospital Severo Ochoa in Madrid, Spain. Subjects. We examined 166 pregnant women (31.6 ± 3.8 years), and all had uncomplicated and singleton gestation. Of these 83 were allocated to the exercise group (EG) and 83 to the control group (CG). Intervention. Women from the EG participated in a physical conditioning program throughout pregnancy, which included 55- to 60-minute sessions, 3 days per week. Measures. Pregnancy outcomes were measured: duration of labor stages, gestational age, weight gain, type of delivery, birth weight, birth size, head circumference, Apgar score, pH of umbilical cord. Analysis. Students unpaired t-tests and y 2 tests were used; p values of < .05 indicated statistical significance. Cohen s d was used to determine the effect size. Results. Significant differences were found in the duration of the first stage of labor (EG = 389.6 ± 347.64 minutes vs. CG= 515.72 ± 353.36 minutes; p= .02, effect size Cohen s d= .36). The second and third stages did not differ between the study groups. Conclusion. A physical exercise program during pregnancy is associated with a shorter first stage of labor. These results may have important relevance to public health.
Artículos en revistas